THE TREND OF ANTIBIOTICS AMONG COMMUNITY-DWELLING OLDER ADULTS (MEDICAL EXPENDITURE PANEL SURVEY 2011–2015). (16th November 2018) - Alotaibi, F; Slattum, P; Mays, D; McRae, M
Abstract: Background: Several studies have suggested that antibiotic overprescribing and misuse increase antibiotic resistance and Clostridium difficile infection. Objectives: The purpose of this study was to determine the trends of infectious diseases and antibiotic use among the community-dwelling older adult population using the MEPS database (2011–2015). A secondary objective was to determine the association between receiving an antibiotic prescription and the patient's demographic characteristics. Methods: A retrospective nationally representative cross-sectional study was conducted to assess the trend of antibiotic use among adults age 65 years and older. Individual characteristics and medication data were obtained from the consolidated data and prescribed medicines files, respectively. Frequency and weighted percentage were reported and multiple logistic regression was performed. Results: Of 18, 121 older individuals, 5, 027 received antibiotic anytime from 2011–2015. Upper respiratory, urinary tract, skin, and gastrointestinal infection were the most commonly reported infections. Rates of infections remained constant over time except for gastrointestinal infection, which decreased significantly from 18.0% in 2011 to 3.6% in 2015. Macrolide use decreased over the study period from 33.5% to 15.6%, while penicillin use increased over time from 17.0% to 26.0%. Being female, less educated, having higher income and visiting the emergency room were significantly associated with receiving an antibiotic prescription, adjusting for other variables. Conclusion: Despite the effort to reduce unnecessary antibiotic use among older adults in order to reduce antibiotic resistance, the overall rate of antibiotic use remained the same within the study period. Further studies are needed to assess the appropriateness of antibiotic use.